1995
DOI: 10.1029/95jb00868
|View full text |Cite
|
Sign up to set email alerts
|

Geodesy using the Global Positioning System: The effects of signal scattering on estimates of site position

Abstract: Analysis of Global Positioning System (GPS) data from two sites separated by a horizontal distance of only ∼2.2 m yielded phase residuals exhibiting a systematic elevation angle dependence. One of the two GPS antennas was mounted on an ∼1‐m‐high concrete pillar, and the other was mounted on a standard wooden tripod. We performed elevation angle cutoff tests with these data and established that the estimate of the vertical coordinate of site position was sensitive to the minimum elevation angle (elevation cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 17 publications
1
133
0
1
Order By: Relevance
“…It should be noted, however, that the intrinsic APV patterns of the antenna/radome pairings in isolation can be significantly altered by near-field effects (multipath and scattering) unique to each terrestrial tracking site. As highlighted by Elósegui et al [1995], the permanent structures (e.g., pillars) to which the antennas are typically mounted become electromagnetically coupled 10.1002 to the antennas themselves. Calibration systems for recovering the comprehensive site-dependent antenna patterns (intrinsic APV plus multipath) have yielded promising results [Park et al, 2004;Wübbena et al, 2006].…”
Section: Using Terrestrial Antennas As Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that the intrinsic APV patterns of the antenna/radome pairings in isolation can be significantly altered by near-field effects (multipath and scattering) unique to each terrestrial tracking site. As highlighted by Elósegui et al [1995], the permanent structures (e.g., pillars) to which the antennas are typically mounted become electromagnetically coupled 10.1002 to the antennas themselves. Calibration systems for recovering the comprehensive site-dependent antenna patterns (intrinsic APV plus multipath) have yielded promising results [Park et al, 2004;Wübbena et al, 2006].…”
Section: Using Terrestrial Antennas As Referencesmentioning
confidence: 99%
“…The near-field multipath can systematically alter the intrinsic APV of the antennas [cf. Figure 4 of Elósegui et al, 1995], and failure to account for these effects can induce significant errors in the estimated station height. The notion that near-field effects may not average down globally-impacting the scale of the whole network-should not be discounted.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…In addition, the effects of unmodelled signal from the reactive near field were studied by Dilssner et al (2008) who also found substantial time-variable noise in GPS coordinate time series. A robust method to model (e.g., Park et al 2004) or mitigate multipath and scattering effects (e.g., Elosegui et al 1995) must be a high priority in the GPS community and similar studies are required for DORIS.…”
Section: Local Site Effectsmentioning
confidence: 99%
“…Multipath-induced errors can appear in many forms: The annual repeat in the GPS satellite configuration could cause an approximately annually ($350 day) repeating multipath signal [Ray et al, 2007]; unmodeled subdaily signals, including those from multipath, could propagate to longerperiod signals [Penna et al, 2007;King et al, 2008]; seasonal signals could be caused by changes in the vegetation, snow pack, and surface water of the local area around the antenna [Dong et al, 2002;Larson et al, 2008]; and changes in multipath could appear or disappear at random as the local environment changes [Dong et al, 2002]. Additional to any effects from far-field reflections, near-field signal scattering by the antenna or monument itself can also be a significant source of error [Elósegui et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…An example in the former category is the so-called ''monument motion'' (discussed below), while examples for the latter include positioning errors caused by multipath (also discussed below), antenna phase center variations [Elósegui et al, 1995;Park et al, 2004], unmodeled atmospheric effects [e.g., Davis et al, 1985;Treuhaft and Lanyi, 1987;Kedar et al, 2003], and satellite orbit errors [e.g., Baueršíma, 1983]. While some of these errors (e.g., atmospheric effects and satellite orbit errors) will have some degree of cancelation over shorter intersite distances, others are noncanceling, site-specific effects (e.g., monument motion and local multipath errors).…”
Section: Introductionmentioning
confidence: 99%